AKIBAT INFEKSI Candida albicans DAN PEMBERIAN KORTIKOSTEROID MENYEBABKAN KONDISI IMUNOSUPRESI ORGAN BURSA FABRICIUS PADA AYAM PEDAGING - Faisal Jamin (Universitas Syiah Kuala, 2012)
Poultry sector remain problemed in animal health system. Several of infectious poultry diseases are spread across regions in Indonesia, such as Avian Influenza (AI), Newcastle Disease (ND), Infectious Bursal Disease (IBD), Cholera, Pullorum, Dwarfism, and Ascariasis. Candida albicans is a flora in a chicken otherwise in immunosuppression (immune system disorder) condition turned into a pathogen. One hundred day old broiler chickens (DOC) into four groups, divided into four groups. Group CC0 (control), fed with basal comercial nutrient, group CC1 chickens fed with basal and infected C. albicans (dose of 105 CFU/ml), group CC2, chickens fed with basal and treated by corticosteroids (3 mg/Kg), group CC3, fed with basal and treated by corticosteroids (3 mg/Kg) and infected C. albicans (dose of 105 CFU/ml). Each group contain 5 replications. Bursa of Fabrisius were collected for histopathology assay using Haematoxylin Eosin stained method. Haematoxylin Eosin stained method applied for HP assay. HP assayed cause Bursa of Fabricius were decreased of their activity. Based on research data obtained, this research concluded that corticosteroids and C. albicans infection resulted decreasing of lymphoid activity of chicken. Corticosteroids and infection C. albicans together were giving lower respon of lymphoid activity compore to each treatment of corticosteroid and C. albicans.